Establishment of experimental sites in three Swedish mines to monitor the in-situ performance of ground support systems associated with mining-induced seismicity - Zhang, Ping; Dineva, Savka; Nordlund, Erling; Hansen-Haug, Jouni; Woldemedhin, Biruk; Töyrä, Jimmy; Boskovic, Mirjana; Nyström, Anders; Marklund, Per-Ivar; Mozaffari, Shahram (Luleå tekniska universitet, Geoteknologi, 2016)
In order to assess the performance of ground support components and systems when subjected to seismic activity and strong ground motion, Luleå University of Technology together with three Swedish mining companies (Lundin Mining, LKAB and Boliden) started a three year research project in September 2014. The aim of the project is to develop new methods for evaluating the rock support performance in-situ that use all available information about i) the source of the seismic event (obtained from the seismic network in the mine and additional seismic sensors), ii) seismic loading (ground motion) recorded by temporary local seismic networks, and iii) the consequences of the seismic loading in terms of damage to the underground excavations and the rock support.The sites with high potential of seismic damage were defined after the historical damaging seismic events were reviewed and the mining-induced stress disturbance was investigated with 3D numerical models. As of 31 December 2015, four sites in three different mines have been instrumented. Geophones (in depth and at surface), multi-points extensometers and instrumented bolts were installed to monitor the ground motion, the deformation of the rock mass and the elongation of the bolts. Observation boreholes were drilled to investigate the rock lithology, structures as well as fracture distribution and development. The data from locally installed geophones will be integrated with seismic data recorded by the mine-wide network. For each monitoring point, all of the instruments and observation boreholes were located at very close area within 0.5-1 m distance from each other. These results will be used to establish the relationship between the dynamic loading and the response of rock mass and rock bolts. Additionally, laser scanning is used to measure the surface deformation of the whole volume of instrumented sites with time. Two damaging seismic events occurred near the instrumented sites after the instruments were installed and the results of site investigation show ...